Synthesis and characterization of rare earth elements cerium and dysprosium doped low density bi-2223 superconductor / Robaiah Mamat - Mamat, Robaiah (2015)
So far, there are limited reports on the investigation on the influence of the rare earth doped low density Bi| 6Pbo 4Sr2Ca2Cu3 0 y system where cerium and dysprosium doping samples possessed a weak connection in the bulk samples. Hence, this study is conducted to investigate the influences of rare earth elements (Ce, Dy) doping on the structural and superconducting properties in low density Bij 6Pbo 4Sr2Ca2Cu3 0 y superconductor. In this research, the influences of cerium and dysprosium doped low density Bi| 6Pbo 4Sr2Ca2Cu3 0 y superconductor were studied based on the best level of low density and sintering time, furthermore, the technique of mixing the superconducting samples with sucrose was used to prepare the low density rare earth elements (Ce, Dy) doped Bi| 6Pbo 4Sr2Ca2Cu3 0 y superconductor. The optimum level of sucrose was found at 0.050 g mixed with 1.950 g of Bi(Pb)SrCaCuO powder while the critical current density, Jc of high density (standard sample) and optimum lowdensity was measured to be 3.746 A/cm 2 and 5.405 A/cm 2 , respectively at 77 K under zero magnetic field. Furthermore, the optimal sintering time of the samples Bii 6Pbo 4Sr2Ca2Cu3 0 v system was found at 850°C for 72 hours. The best Jc achieved in high density and optimal low density samples were 7.547 A/cm 2 and 8.333 A/cm 2 respectively at 77 K under zero magnetic fields. However, it was found that both doped Ce and Dy at Ca site indicated deteriorations on the superconducting properties when compared with the undoped samples. The doping samples exhibited the increased values of 7c and Jc towards the optimum concentration and decreased after the further increase of Ce and Dy dopants.